Effect of Dietary Calcium and Age on Jejunal Calcium Absorption in Humans Studied by Intestinal Perfusion - Ireland, Patricia (1973)
Jejunal calcium absorption was measured from test solutions containing 1.0, 2.5, 5, and 10 mM calcium (as calcium gluconate). Absorption rates increased progressively as luminal calcium concentration was increased, although there was a tendency toward saturation of the absorptive process at the higher concentrations. Calcium absorption was higher in normal young adults than in normal subjects over age 60. In both groups a 300 mg calcium diet for 4-8 wk enhanced calcium absorption relative to absorption rates after 4-8 wk on a 2,000 mg calcium diet. This adaptation was more definite and dramatic in the young than in the old subjects. Indirect estimates suggest that adaptation to a low calcium diet and the higher absorption in young than old normal subjects are mediated by an increased V(max) rather than a decreased K(m).